The Development of Inquiry-Based STEM Instructional Modules on Students’ Critical Thinking Skills in Geometry and the Application of Water Purification Processes - Sajawiyah, Hosiatus; Lestari, Wahyu; Zairozie, Athar Zaif (Faculty of Teacher Training and Education, 2026)
Students’ critical thinking skills in mathematics are not yet optimally developed, particularly in geometry learning, which is often presented in an abstract manner with limited connection to real-life contexts. This study aimed to develop a STEM-integrated instructional module based on an inquiry-oriented learning framework for three-dimensional geometry using a water purification context to create more meaningful learning experiences. The study employed a development research design using the ADDIE framework, which consists of five phases: analysis, design, development, implementation, and evaluation. The participants were 20 ninth-grade students from a lower secondary school (SMP Mambaul Ulum). Data were collected through expert validation forms, student response questionnaires, and a critical thinking skills test to evaluate the module’s validity, practicality, and effectiveness. The findings revealed that the developed module met the required criteria. It demonstrated a high level of validity, with a score of 82%. The practicality of the module improved from 65% in the initial trial to 75% after revision. Furthermore, its effectiveness was reflected in the improvement of students’ critical thinking skills, with mastery levels increasing from 75% to 85%. Overall, the results indicate that the inquiry-based STEM module is both appropriate and effective as an instructional resource, as it supports learning that is closely connected to real-life contexts and enhances students’ critical thinking skills in three-dimensional geometry.